Greeks Express Mixed Views of EU. - United States Information Agency. Office of Research and Media Reaction. (Tufts University. Tisch Library., 2019)
Despite a tendency to view major international organizations negatively, Greeks are not wholly negative in their image of European unification and they are more likely than ever to think they will soon be part of the EMU.; European Opinion Alert L-56-99